Risk Assessment Of Loan Pricing (A Case Study at PT. Bank Rakyat Indonesia Malang Kawi Branch Office) - Ramadhan, Rizki (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The tight competition in banking sector has stimulated banks to initiate breakthrough by providing a wide range of banking products and facility to their customers. This undeniably effects the assessment of loan pricing and credit risk. The purpose of this study is to understand the methods used by a bank in loan pricing and credit risk analysis. In addition, this study is aimed to find out whether the effect of the magnitude of inherent risks have a role in determining the credit interest rate. This research employs descriptive qualitative as the research method in which the object under study is PT. Bank Rakyat Indonesia Malang Kawi Branch Office. This study focuses on the process of credit retail realization, specifically on credit risk assessment. Based on the analysis, the findings show that PT. Bank Rakyat Indonesia uses two methods in the analysis of credit risk. The methods are 5C’s and Credit Risk Rating (CRR). It was found that the implementation of the methods were in line with the Basel Principles formulated by the Basel Committee on Banking Supervision. Credit analysis process is also used by the bank as a reference in determining lending rates. Keywords: Credit Bank, Loan Pricing, Credit Risk, Credit Risk Analysis.